Effect of pulse time and external magnetic field on Giant Magnetoresistance (GMR) effect of electrodeposited multilayer Co/Cu - Tung, Mai Thanh; Nghi, Nguyen Hoang (Vietnam Journal of Chemistry, 2014)
Influences of pulse time and external magnetic on Giant Magnetoresistance (GMR) effect of multilayer Co/Cu were investigated. Results showed that by changing pulse deposition time (tCo, tCu), the MR ratio of the electrodeposited multilayers varied from 0 to 2.70%. The maximum value of MR ratio (2.70%) was achieved with deposition time (tCo= 2s, tCu= 5s), corresponding to the thickness (δCo = 2.1 nm, δCu= 7.0 nm). The presence of external magnetic field Hext during electrodeposition enhanced the amount of deposited Cu on one hand, and increased the (200) texture of the deposited films on the other hand. As a result, the MR ratio of the obtained multilayers increased slightly from 2.70% (Hext= 0) to 2.74% (Hext= 600 mT).